A COMPARATIVE STUDY OF ANTIOBESITY PROPERTY OF BARLEY AND OAT FLOUR - Rajesh, Kumari; Satish, Gupta; Vivek, Jain; Abhisheak, Sharma; Mita, Kotecha (International Journal of Ayurveda and Pharma Research, 2015)
The present study was designed to evaluate the effect of flour barley and Oat (Family- Poaceae) on body weight and associated metabolic disorder in over weight human volunteers. The study participants comprised of 48 healthy, over weight (defined as BMI>23/m2) human volunteers divided in two groups, of age group 20-60 years, in a dosage of 150 g, in a form of chapatti once in a day for two months. Anthropometrics, hematological and subjective parameters were carried out in the beginning and also at the end of the trial. The single blind trial was conducted for 2 months. Significant improvement in Body weight, BMI, BMR, Visceral fat, Body fat, Lipid profile, Skin fold thickness was observed in both Barley flour group and Oat flour group, but Barley flour group is found to be more effective than Oat flour group. Barley flour in the form of chapatti to overweight human volunteers shown favorable impact on body weight and a variety of parameter characteristic of the metabolic syndrome.